Effects of different inspired oxygen fractions on sildenafil-induced pulmonary anti-hypertensive effects in a sheep model of acute pulmonary embolism - Becerra Velasquez, Diana Rocio [UNESP]; Teixeira-Neto, Francisco Jose [UNESP]; Lagos-Carvajal, Angie Paola [UNESP]; Steim-Diniz, Miriely [UNESP]; Rodriguez, Nathalia Celeita [UNESP]; Dias-Junior, Carlos Alan [UNESP] (Elsevier B.V., 2015)
Aims: Sildenafil is a pulmonary anti-hypertensive agent whose action could be modified by different fractions of inspired oxygen (FiO(2)). We compared the effects of pure oxygen (FiO(2) > 90%) or room air (21% FiO(2)) on the cardiopulmonary actions of sildenafil in sheep with acute pulmonary embolism (APE).Main methods: Forty anesthetized, mechanically ventilated sheep (34.9 +/- 5.4 kg), were randomly distributed into four groups (n = 4 per group): FiO(2) > 90% without intervention; APE induced by microspheres with FiO(2) > 90%, followed 30 min later by placebo (Emb(90)); or APE followed 30 min later by intravenous sildenafil (0.7 mg/kg over 30 min) with FiO(2) > 90% (Emb + Sild(90)) or 21% FiO(2) (Emb + Sild(21)). Variables were recorded until 30 min after the end of treatment administration.Key findings: Microsphere injection increased (P < 0.05) mean pulmonary artery pressure (MPAP) in all embolized groups (111-140% higher than that of baseline). Compared with values recorded 30 min after induction of APE (E-30), sildenafil induced greater decreases in MPAP in the Emb + Sil(90) group than in the Emb + Sil(21) group (23% and 14% lower than E-30, respectively). Hypotension (mean arterial pressure <60 mm Hg) Hg) was precipitated by sildenafil due to systemic vasodilation in the Emb + Sil(21) group. Embolization lowered the PaO2/FiO(2) ratio and increased venous admixture, but sildenafil did not alter the oxygenation impairment induced by APE.Significance: Sildenafil induces a more consistent pulmonary anti-hypertensive effect and causes less interference with the systemic circulation with the concomitant use of pure oxygen than that with room air in the APE setting. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Acute pulmonary embolism; Sildenafil; Pulmonary hypertension